Pelatihan Simulasi Platform Elektronik Wokwi Berbasis Web Pada Rangkaian Mikrokontroler Arduino - Rahmat Nursiaga; Imam Santoso; Nana Mulyana; Muhidin Muhidin; Siti Madinah Ladjamuddin; Erdita Naffisa Eriyani; Rifqih Rizqullah (Jurnal Pengabdian Kepada Masyarakat, 2026)
Practice-based learning models, especially those using tools, have proven to be easier for students to understand, especially when the material is technical. Challenges arise when practical tools must be purchased, and costs are often high. Therefore, the existence of Wokwi as a virtual simulation platform for Arduino Microcontrollers is an effective solution to overcome the constraints of equipment procurement, so that practical learning continues to run well and optimally. The purpose of this Community Service (PkM) is to broaden the insight of students of SMAN 92 Jakarta Utara regarding the use of the Wokwi Web-based Arduino microcontroller simulator application, thus enabling virtual learning without the need for physical devices or sensors. With this approach, students of SMAN 92 North Jakarta can understand the concept of Arduino microcontrollers practically, thereby eliminating the constraints of cost and availability of tools. This community service activity ( PkM ) was carried out using lecture methods and science and technology simulations. Based on the Post Test Results of 271 students, 81.40% of students of SMAN 92 Jakarta located at Jl.Pemadam Api Semper Barat, Cilincing, Jakarta Utara City, Daerah Khusus Jakarta understood the activity material presented, thus the results of this PkM are in the good category. Keywords : Arduino, Microcontroller, Simulator, Wokwi.